Pertunjukan Body Painting di Bali sebagai Objek Pariwisata - I Nyoman Rediasa; Langen Bronto Sutrisno (Jurnal Kajian Seni, 2016)
The purpose of this study, to uncover and describe the aesthetic form and functionof body painting in Bali in Bali tourism. The Study is designed throgh qualitativeresearch to describe the Body painting show in Bali tourism in terms of postmodern aesthetics. The research location is at the HardRock Hotel Bali. Theoretical approachesto understand the body painting uses studies in popular culture, postmodern aestheticsand commodifi cation. The organized form of body painting HardRock Hotel Balisince2003 is a creative body painting event on women and performance art, that includesactivities of the female body painting art ist fashion shows of the painting accompaniedby music. The function of body painting Bali accomodates tourism interests, and itoccurs through the commodifi cation of popular culture in the pack includes the functionof personal, social, (recreation and appreciation).